(untitled) (Research, Society and Development, 2021)
Objective: This study aims to present the preventive orthodontic treatment of a child with mixed dentition with early loss of primary teeth through the use of space maintainers. Methodology: Based on the patient’s permission through the Informed Consent Form (FICF) to share her image for the proper purpose, this study is a clinical case report of a descriptive analytical nature (Pereira et al., 2018). Clinical Case Report: A 7 years and 5 months old male patient, brown, attended the Comprehensive Child Care clinic accompanied by his mother, complaining of pain in element 55. He presented poor oral hygiene and multiple carious lesions, with the plan of treatment measures to promote oral health, restorations and extractions, followed by the installation of space maintainers, due to early extraction, to avoid future occlusal problems, as its effectiveness has already been proven. Final Considerations: Thus, the use of space maintainers is extremely necessary.